2007
DOI: 10.1042/bj20070286
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of hypoxia-inducible factor 1 in human T-cell leukaemia virus type 1-infected cell lines and primary adult T-cell leukaemia cells

Abstract: HTLV-1 (human T-cell leukaemia virus type 1) is the causative agent for ATL (adult T-cell leukaemia). HTLV-1 Tax can activate the PI3K (phosphoinositide 3-kinase)/Akt signalling pathway, which is responsible for survival of HTLV-1-infected T-cells. HIFs (hypoxia-inducible factors) are transcriptional regulators that play a central role in the response to hypoxia. Overexpression of HIF-1alpha in many cancers is associated with a poor response to treatment and increased patient mortality. Our objectives in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…In this regard, it has been shown that HIF-1␣ can be induced and accumulated in cells infected with HTLV-1 and HHV8 (46,47). Furthermore, HIF-1␣ was also shown to be suppressed in cells infected with a temperaturesensitive Moloney murine leukemia virus mutant (48).…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, it has been shown that HIF-1␣ can be induced and accumulated in cells infected with HTLV-1 and HHV8 (46,47). Furthermore, HIF-1␣ was also shown to be suppressed in cells infected with a temperaturesensitive Moloney murine leukemia virus mutant (48).…”
Section: Discussionmentioning
confidence: 95%
“…This apoptosis is related to a reduction of the DNA binding of NF-B and AP-1 and to a down-regulation of Bcl-x L and cyclin D2 expression in HTLV-1-infected T-cells [55]. The same apoptosis effect could be related to inhibition of HIF-1 by HDACi able to inhibit the class II HDACs [56], because HIF-1 has been shown to be highly activated in HTLV-1-infected T-cells [57].…”
Section: B) Reversal Of Hiv-1 Latency With Hdac Inhibitorsmentioning
confidence: 92%
“…bacterial interactions can induce HIF-1 signaling in some cells. For example, human T-cell leukaemia virus (HTLV)-1 [19], Epstein-Barr virus [20,21], Hepatitis B virus [22][23][24][25][26] and Kaposi's sarcoma-associated herpes virus [27][28][29] use a variety of molecular strategies to increase HIF-1 expression and/or transcriptional activity. In addition to viruses, a variety of bacteria and their products, especially lipopolysaccharide (LPS), up-regulate HIF-1 expression in a number of cell types [30][31][32][33][34] Fig.…”
Section: Normoxic Induction Of Hif-1 Signaling During Inflammationmentioning
confidence: 99%